BUSINESS ETHICS IN THE CONCEPT OF SHARIA LAW - Sayyidatunisa Sayyidatunisa; Reni Seri Lestari; Shella Titania Nurdin; Masruroh Masruroh; Indah Nur Anisa; Fitri Nur Latifah (Ad-Deenar: Jurnal Ekonomi dan Bisnis Islam, 2020)
In the information ethical Islamic banks, both quantitative and qualitative in aspects of moral and material in terms of the market share of sharia banking in Indonesia is still relatively small in comparison with the share of the conventional market, but in Islamic banking has an annual growth rate which is quite significant, and on the Development of the market share of sharia is quite encouraging but have not yet followed with the application of the principles of business ethics of Islam which is the maximum. However, Islamic banks have implemented the principles of Islamic business ethics in their operations. They have also provided a guide to the stakeholders, such as customer depositors, shareholders, investors, bonds, bank respondents, the regulator, employees of the company, suppliers, and the environmental community to realize public accountability in its efforts to economic decisions.